PENINGKATAN KERJA ILMIAH SISWA KELAS II SD DENGAN PENGEMBANGAN PEMBELAJARAN TEMATIK - Pitadjeng, - (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2010)
This study was aimed at knowing the development and effectiveness of the thematic learning model in elementary school students’ class work. The research was conducted in two phases. The first phase involved the development of the thematic learning model using the 4-D mode. The second phase involved the implementation of the model in the schools using the classroom action research mode. The subjects were 19 students of Sekayu 2 Elementary School and 43 students of Tambakaji 3 Elementary School, both in Semarang. Observations were conducted on students’ class work, students’ learning activities, and students’ learning achievement. Data were analyzed descriptively. The results of the study showed that the implementation of the thematic learning model improved students’ class work from the low ratings of 1, 7 and 1, 44 to 3, 2 and 3, 06.